2019
DOI: 10.1002/ecs2.2895
|View full text |Cite
|
Sign up to set email alerts
|

Novel management tools for subsidized avian predators and a case study in the conservation of a threatened species

Abstract: Wildlife managers face complex problems in attempting to achieve contemporary conservation goals while maintaining ecosystem function. Anthropogenically altered environments can subsidize certain species, causing them to become overabundant and straining the remaining natural system. Such is the case with the widespread avian generalist and subsidized predator, the common raven (Corvus corax). Ravens depredate nests and prey on small animals, with locally focused high impacts to the ecosystem during rearing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The posterior estimates of the TFD and AWT models presented herein are directly incorporable for designing and implementing new occupancy surveys within cliff habitat of the Appalachian region and eastern United States. The effectiveness of the time‐to‐detection method for estimating detectability and abundance makes this framework conducive to raven monitoring not only for targeted species conservation but also for management and control in ecosystems where ravens depredate species of concern, such as the threatened desert tortoise ( Gopherus agassizii , Cooper) in the Mojave Desert, USA (Kristan & Boarman, 2003; Shields et al, 2019); spur‐thighed tortoise ( Testudo graeca L.) in Morocco (Segura et al, 2020); and greater sage‐grouse ( Centrocercus urophasianus , Bonaparte) in the western United States (O'Neil et al, 2018). To utilize the time‐to‐detection framework for survey planning in other geographic areas, studies similar to ours that evaluate detection patterns should be repeated to derive accurate location‐specific detectability curves and recommendations of required survey effort.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior estimates of the TFD and AWT models presented herein are directly incorporable for designing and implementing new occupancy surveys within cliff habitat of the Appalachian region and eastern United States. The effectiveness of the time‐to‐detection method for estimating detectability and abundance makes this framework conducive to raven monitoring not only for targeted species conservation but also for management and control in ecosystems where ravens depredate species of concern, such as the threatened desert tortoise ( Gopherus agassizii , Cooper) in the Mojave Desert, USA (Kristan & Boarman, 2003; Shields et al, 2019); spur‐thighed tortoise ( Testudo graeca L.) in Morocco (Segura et al, 2020); and greater sage‐grouse ( Centrocercus urophasianus , Bonaparte) in the western United States (O'Neil et al, 2018). To utilize the time‐to‐detection framework for survey planning in other geographic areas, studies similar to ours that evaluate detection patterns should be repeated to derive accurate location‐specific detectability curves and recommendations of required survey effort.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the artificial nest predation experiments, corvids are often perceived as efficient nest predators that directly impact the populations of other bird species [ 153 , 154 ]. Despite this perception, relatively few experimental removal or population control studies have been performed in corvids [ 151 , 155 , 156 , 157 ]. Most of these studies found that the overall impact of corvid species on nest predation rate of other species is rather small, and that the populations of other bird species are less likely to be limited by corvid predation than suspected before.…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of these birds and their high flexibility makes them targets to persecution by shooting [ 26 , 125 , 162 , 163 , 164 ]. Other examples of management include the destruction of Chihuahuan ( Corvus cryptoleucus ) and Common Ravens nests on electric poles [ 156 , 169 , 170 ], scaring away winter roosts of American Crows in U.S. cities [ 124 , 165 ] and trapping and removal of Hooded Crow and Carrion Crow individuals in cities in Europe [ 166 , 167 , 170 ]. However, the current population status of these species indicates that the success of these management efforts so far is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few ravens were killed or removed in the western Mojave Desert or Natural Area during our study, however (USFWS, Desert Tortoise Recovery Office, Reno, Nevada, unpublished reports). The latest effort of oiling eggs in raven nests using drones was confined to natural surfaces (cliffs, Joshua trees; Shields et al 2019). Excluded were utility towers or humanconstructed facilities where nests are common Kawashima 1993, Knight et al 1999).…”
Section: Management Implicationsmentioning
confidence: 99%